2022
DOI: 10.3389/fnut.2022.976020
|View full text |Cite
|
Sign up to set email alerts
|

Fermented foods and cardiometabolic health: Definitions, current evidence, and future perspectives

Abstract: Unhealthy diets contribute to the increasing burden of non-communicable diseases. Annually, over 11 million deaths worldwide are attributed to dietary risk factors, with the vast majority of deaths resulting from cardiometabolic diseases (CMDs) including cardiovascular disease (∼10 million) and type II diabetes (∼339,000). As such, defining diets and dietary patterns that mitigate CMD risk is of great public health importance. Recently, the consumption of fermented foods has emerged as an important dietary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…The authors of this work have a particular awareness that the consumption of dairy, particularly low-fat dairy, is advocated in most dietary guidelines worldwide. Still, there is, therefore, a necessity to expand such research could eventually have an impact on public health, such a refining guidelines, especially for fermented dairy foods, and a better understanding of the composition of different fermented food products as part of healthy, sustainable diets [ 17 , 29 ]. This approach can help convince consumers that consuming fermented dairy products helps maintain health and prevent disease ispart of an effort to increase life expectancy and improve life quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this work have a particular awareness that the consumption of dairy, particularly low-fat dairy, is advocated in most dietary guidelines worldwide. Still, there is, therefore, a necessity to expand such research could eventually have an impact on public health, such a refining guidelines, especially for fermented dairy foods, and a better understanding of the composition of different fermented food products as part of healthy, sustainable diets [ 17 , 29 ]. This approach can help convince consumers that consuming fermented dairy products helps maintain health and prevent disease ispart of an effort to increase life expectancy and improve life quality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that diet influences the structure and function of the gut microbiota [ 14 , 15 ]. It is believed that the consumption of fermented foods containing probiotics—“live microorganisms which, when administered in adequate amounts, confer a health benefit on the host” [ 16 , 17 ]—is an effective way to introduce potentially beneficial microorganisms to the intestinal tract and help manage a wide range of disorders. Those among others include disorders associated with gut microbial dysbiosis, such as behavior and (gut-)brain disorders, inflammatory bowel disease, irritable bowel syndrome, and coeliac disease, as well as extra-intestinal disorders, including allergy, asthma, obesity, metabolic syndrome, cardiovascular disease and cancer [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some foods are subjected to pasteurization, smoking, baking, or filtering after fermentation, causing live microorganisms to die or be removed. Sourdough bread (baked), shelf-stable pickles (heated), sausages (heated), soy sauce (heated), vinegar (heated), most beers, distilled spirits (filtered), coffee and chocolate beans (roasted) are fermented products (Li et al 2022 ). Still, microorganisms have died or been eliminated from fermentation.…”
Section: Fermented Dairy Productsmentioning
confidence: 99%
“…In some cases, epidemiological data point towards that certain food items or food groups are associated with distinctive and unique health-promoting effects as their intake is associated with a lowering in the risk of developing lifestyle diseases. An example is fermented foods; weighty evidence points at fermented dairy exerting unique health-promoting effects including improved cardiometabolic health [39]. Du et al [40 ▪ ] recently employed NMR metabolomics to identify effects of yogurt consumption in obese women with metabolic syndrome and nonalcoholic fatty liver.…”
Section: Specific Dietary Itemsmentioning
confidence: 99%